1997
DOI: 10.1002/(sici)1096-9136(199707)14:7<603::aid-dia406>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcome of Hyperglycaemic Emergencies in Johannesburg Africans

Abstract: Apatitic tricalcium phosphate was used as support for supported aqueous phase catalysis (SAPC) in the hydroformylation reaction of oct‐1‐ene, at 80 °C in toluene using a dinuclear rhodium complex bearing TPPTS as hydrophilic ligands. The reaction yield is maximum and constant when the hydration rate of the support is ranging from 20 to 35%, before starting to decrease dramatically. The support was examined initially and after catalytic runs by XRD, FTIR, 1H and 31P NMR, SEM and EDS. No change was observed when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 2 publications
(2 reference statements)
0
25
0
Order By: Relevance
“…50,51 The majority of patients demonstrate progressive b-cell failure. This is in keeping with the concept that black Southern Africans either inherit or acquire a decreased pancreatic beta cell mass, 52 and that the functional ability of these b-cells will become rapidly exhausted when glucose intolerance supervenes, with many of the patients requiring insulin therapy to initially restore normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 The majority of patients demonstrate progressive b-cell failure. This is in keeping with the concept that black Southern Africans either inherit or acquire a decreased pancreatic beta cell mass, 52 and that the functional ability of these b-cells will become rapidly exhausted when glucose intolerance supervenes, with many of the patients requiring insulin therapy to initially restore normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with the concept that black Southern Africans either inherit or acquire a decreased pancreatic beta cell mass, 52 and that the functional ability of these b-cells will become rapidly exhausted when glucose intolerance supervenes, with many of the patients requiring insulin therapy to initially restore normoglycemia. 50 Furthermore, in South Africa, newly diagnosed type 2 black diabetics treated with sulphonylurea therapy demonstrated an increase in insulin receptor concentration, but showed no changes in basal insulin secretion. 53 In the present study, endogenous b-cell secretory function in the black women appears to be more sensitive to the suppressive effect of exogenous insulin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic type 1 diabetes has been described mostly in African-Americans but also in individuals from other ethnic groups (21)(22)(23)(24)(25)(26). The majority of these patients are been treated as if they have type 2 diabetes (1,2,4,16).…”
mentioning
confidence: 99%
“…19 Infection, known or undiagnosed especially of the urinary tract, respiratory tract and skin is the most common precipitating factor causing more than 50% of identified causes. [4][5][6][7] Zouvanis et al in 1997 reported in Johannesburg Africans that infection was the leading precipitating factor for both DKA and HHS 20 while Umpierrez et al in the same year, in Atlanta also reported infections in 34% of patients presenting with diabetic emergencies. 21 Omissions or inadequate doses of insulin are frequent precipitating factors, particularly for DKA.…”
mentioning
confidence: 99%
“…Often patients mistakenly take less insulin because of decreased food intakes, thus magnifying the effects of the catabolic hormones. 2,3,[18][19][20][21][22] …”
mentioning
confidence: 99%